2018
DOI: 10.1016/j.buildenv.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study on airborne disinfection by negative ions in air duct flow

Abstract: In this paper, we develop a mathematical model that aims (1) to predict the distribution of negative ions generated by an air ionizer installed in a ventilation duct and (2) to predict the efficiency with which it inactivates bacteria. The transportation equation for the negative ions was resolved combined with the bulk air velocity and the electric field.The bacteria distribution was solved numerically by integrating the susceptibility constant, which was acquired from the experiments. Two types of bacteria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…There are many references to report the possible biological effects [ 24 , 32 , 33 , 35 , 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. And some of them were listed in Table S2 .…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%
“…There are many references to report the possible biological effects [ 24 , 32 , 33 , 35 , 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. And some of them were listed in Table S2 .…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%
“…Consequently, their findings on the inactivation effectiveness of UV lamps and susceptibility (Z value) of bacteria to UV may have limited applicability for in-duct UV lamps in real ventilation ducts, where turbulent airflows and various environmental conditions are commonly involved. 19,20 Temperature may also play a critical role in influencing the effectiveness of sterilization by in-duct UVC lamps. UV output is highly dependent on the mercury vapor pressure of the UV lamp.…”
mentioning
confidence: 99%
“…This NAI concentration is between the NAI concentration produced in forests and that produced in waterfalls, indicating its favorable healing and recovery effects [52]. Zhou et al [53] have demonstrated that NAIs also have great potential for enhancing indoor air quality by reducing airborne microorganisms in ventilation systems. Wu [2] also demonstrated that NAIs can eradicate particulate matter.…”
Section: Nai Concentrations Observed For Different Waterscape Designsmentioning
confidence: 99%